Children and Separation : Socio-Genealogical Connectedness Perspective. - Owusu-Bempah, Kwame (Routledge, 2014)
Childhood separation and loss have become virtually a way of life for a large number of children throughout the world. Children separated from their genetic parent(s) and consequently their genealogical, social and cultural roots due to processes such as adoption, parental divorce/separation, donor insemination, single parenthood by choice and child trafficking can face social, emotional and psychological difficulties. This book explores the premise that a proper understanding of the complex inner world of modern day separated children and their psycho-social development requires a shift in foc.